Thrills, spills and pills: Bond, Benzedrine and the pharmacology of peace. Issue 1 (9th June 2010) - Goodman, Sam
Abstract : This paper examines the conjunction of pharmacological science and espionage fiction of the post-war era. This paper argues that, during the 1950s, the relatively new science of pharmacology propounded the possibility that illness and human deficiency could be treated in a way that better reflected the post-war zeitgeist. The use of pharmacological medicine, perceived as cleaner and quicker than more 'bodily' forms of treatment, represented progress in contemporary medical science. It is argued that this philosophy extended to more overt means of pharmacological application, directly related to the geopolitical concerns of the 'Cold War'. A growing form of popular literature in this period was the espionage novel. This paper argues that the benefits proffered by pharmacology were incorporated into the fabric of espionage fiction, specifically the James Bond novels of Ian Fleming. Here, it is demonstrated how Fleming used pharmacological knowledge of Benzedrine throughout his novels. His works illustrate a belief that the augmentation of the spy's natural ability with pharmacological science would award decisive advantage in the Cold War conflict played out in spy fiction. However, the relationship between public use of Benzedrine and awareness of its side effects changed during the period of Fleming's publications, moving from a position of casual availability to one of controlled prescription. It is argued that the recognition of the dangers associated with the drug were over-ruled in favour of the benefits its use presented to the state. The continued use of the drug by Bond illustrates how the concerns of the nation are given priority over the health, and life, of the individual.